Early Medieval Dvin: Some preliminary remarks - Petrosyan , Hamlet (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
As a rule, in Armenian studies Dvin is presented as a separate initiative related to the stagnation around Artashat and the relocation of the court. New researches give grounds to consider Dvin as a component of the royal domain, which together with Artashat, Garni and Vagharshapat formed an administrative and economic-cultural unit. The early medieval Dvin was formed as a factor that completed the complex of the Ararat Valley and especially formed its Christian image. In this regard, the myth of the conversion of Armenians is of special interest, which includes Artashat, Vagharshapat, Garni and the newly created Dvin in the Christian sacred landscape. The formation of the early Christian district of Dvin and its relations with the early Christian squares of Vagharshapat, Aruch and Tigranakert of Artsakh deserve special interest. The examination of Dvin’s trade-economic and water supply systems are no less important. It shows the way how Dvin became one of the most important commercial-economic centers of the region. The article will also present the results of the recent years’ archaeological research of Dvin, in particular the results of the excavations of the Dvin market and defensive trenches, as well as the perspectives of further research.